Doctor-Patient Therapeutic Agreement in the Perspective of Law No. 29/2004 and Islamic Law - Ahmad Faisal; Adang Djumhur Salikin (Ann Publisher, 2025)
Background. The relationship between doctors and patients is not only a technical-medical relationship, but also a complex legal and ethical relationship. As public awareness of patients' rights increases, the relationship demands legal certainty that protects both parties. In the context of Indonesian law, this relationship is attached in the form of a therapeutic agreement, which is an agreement between the doctor and the patient regarding the medical procedure to be performed, the rights and obligations of each party, and the legal consequences if the agreement is violated. Purpose. This study discusses the therapeutic agreement between doctors and patients in the perspective of Law No. 29 of 2004 concerning Medical Practice and Islamic law. The focus of the study lies on the common points, differences, and possible integration of the two in medical practice in Indonesia. Method. This study uses a normative-comparative approach by analyzing regulations, jurisprudence, MUI fatwas, and classical fiqh books. Result. The results of the study show that according to Law No. 29/2004, the doctor-patient relationship is a legal contract that requires informed consent, professional standards, and accountability mechanisms. Meanwhile, Islamic law views it as a valid ijārah (service hire contract) if it fulfills the pillars of the contract, with the principles of tarāḍī (willingness), gharar (ambiguity), and ḍarar (danger). Jurisprudence emphasizes the principle of inspanningsverbintenis (the obligation of maximum effort, not results), while the MUI fatwa emphasizes the aspects of ridā, trust, and the welfare of the soul. The integrative synthesis offered places Law No. 29/2004 as the basis for formal legality, Islamic law as moral-religious legitimacy, and jurisprudence and fatwa as operational bridges. Thus, therapeutic agreements are not contradictory, but complementary in realizing legal, ethical, and spirituality-based medical practices.